Pengaruh Upah Terhadap Semangat Kerja Supir Di PT. Nusantara Balawan Logistik Cabang Pelalawan Kerinci - Fuaddi, Husni; Simbolon, Tahan Theo (EL-EMIR Institute, 2025)
The objectives to be obtained in this study are 1) To determine the effect of wages on the morale of drivers at PT. Nusantara Balawan Logistics Pelalawan Kerinci Branch. 2) To determine the effect of incentives on the morale of drivers at PT. Nusantara Balawan Logistics, Pelalawan Kerinci Branch and 3) To determine the effect of wages and incentives together on the morale of drivers at PT. Nusantara Balawan Logistics Pelalawan Kerinci Branch. This research was conducted on all employees at PT. Nusantara Balawan Logistics, Pelalawan Kerinci Branch, totaling 30 people. Considering that the population is large, the sampling technique is when the entire population is used as a sample and is also known as a census, if the total population is less than 100 people, then the total sample is taken as a whole. In this study, 30 drivers will be the sample. The data analysis technique used is multiple linear regression analysis. Based on the results of the research that has been done, it is concluded that the calculated F value is 15,860 greater than Ftable which is 3.34 with a probability of 0.000 less than 0.05 and the obtained value of Fcount> Ftable is obtained by looking at table F using a 95% confidence level , α = 5%, the value of df1=k- 1(3-1)=2, and df2= (n-k)= 30-2= 28. Then the value of Ftable is 3.34. Thus the value of Fcount> Ftable (15,860 > 3.34) is obtained. Based on the hypothesis testing criteria, H0 is rejected and Ha is accepted, that is, together the independent variables have a significant effect on the dependent variable. The wage and incentive variables together have a significant effect on employee morale at PT. Archipelago Balawan Logistics Pelalawan Kerinci.